Financial Inclusion through Mobile Micro Banking: Building a Prototype for Transaction Cost Efficiency in Microfinance Practice - Hussain , A H M Belayeth (Global Disclosure of Economics and Business, 2017)
The present paper briefly reviews and emphasizes numerous faceted costs fitting to transaction and administration brought about by financing techniques of a microfinance establishment. The paper likewise proposes a model that can utilize the digital device to diminish different expenses including social capital, observation and approvals. The paper proposes that this model can be an option road for financial inclusions and repayment achievement of lending establishments at the expense cost of transaction and administrative cost.